The Role of Community Participation, Accountability, and Transparency on the Effectiveness of Village Fund Management - Divtita Sofia; Hadiah Fitriyah (Indonesian Journal of Cultural and Community Development, 2022)
This study aims to provide empirical evidence regarding the Role of Community Participation, Accountability, and Transparency on the Effectiveness of Village Fund Management by examining each variable. The object of this research is in the District in Sidoarjo District, namely Prambon District. This study uses a quantitative method with a non-probability sampling technique with purposive sampling involving 10 villages in Prambon District with 100 respondents as the research sample. The analytical model used is a multiple linear regression analysis model which was carried out with the help of SPSS version 26 for windows. The results of this study indicate that community participation, accountability and transparency affect the effectiveness of village fund management.